Empathic attitudes among nursing students: a preliminary study - Ferri, Paola; Rovesti, Sergio; Panzera, Nunzio; Marcheselli, Luigi; Bari, Alessia; Di Lorenzo, Rosaria (Acta Biomedica Atenei Parmensis, 2017)
Background and aim. An empathic approach is fundamental for therapeutic relationship between nurse and patient. According to some researchers, female nursing students show higher empathic attitude in comparison with males, but both show a decline in empathy level as their studies progress. This preliminary study evaluated the self-reported emotional empathy level among undergraduate students at first and second year of nursing 3-year course. Method. To assess empathy level, the Balanced Emotional Empathy Scale (BEES) was administered to all students enrolled in the 2015/16 academic year (N=142), at the beginning of first year (T0) and at mid-point of second year (T1) of nursing course. Data were statistically analyzed. Results. 118 nursing students participated in the first and 99 in the second survey. The BEES global mean score for the longitudinal group (n=99) slightly decreased  from T0 (mean=37.1±19.5 SD) to T1 (mean=33.5±22.6 SD) (t=1.20, p=0.23; t-test for paired data). Female students reported a statistically significant higher mean BEES score compared to male students in both surveys. Conclusions. Our preliminary data suggest a slight decline in empathy level among nursing students with the progress of study course, in accordance with  previous studies. In particular, our study shows higher levels of empathy in female students and lower levels in male students, compared to other studies.  Further surveys aimed at investigating the empathy attitude at the end of nursing course could confirm the decline tendency reported by this preliminary study. Other research focusing on the causes of empathy decline are necessary to explain this phenomenon.